2012
DOI: 10.1002/mus.23259
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain in post‐burn hypertrophic scars: A psychophysical and neurophysiological study

Abstract: In PPS, possible neuropathic pain is associated with psychophysical and neurophysiological abnormalities suggestive of small-fiber damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…4 Patients with these symptoms typically have decreased IENF density in post-burned skin. 5 Similar QST responses to those found by us were shown in hypertrophic skin scars in Letters to the Editor patients after burn injuries 6 and indicate a sensory impairment of small fibre function. Together with the decreased IENF, we have strong indication that our patient presents a typical form of small fibre neuropathy caused by burn injury and skin grafts thereafter including a pathologic reaction towards temperature.…”
supporting
confidence: 72%
“…4 Patients with these symptoms typically have decreased IENF density in post-burned skin. 5 Similar QST responses to those found by us were shown in hypertrophic skin scars in Letters to the Editor patients after burn injuries 6 and indicate a sensory impairment of small fibre function. Together with the decreased IENF, we have strong indication that our patient presents a typical form of small fibre neuropathy caused by burn injury and skin grafts thereafter including a pathologic reaction towards temperature.…”
supporting
confidence: 72%
“…The underlying cause of this phenomenon is abnormal nerve fiber function of small fibers (C‐fibers, Ad‐fibers) as demonstrated by quantitative sensory testing (QST). In patients with post‐burn scars and keloids , pathological thermal thresholds reflecting neuropathic sensory dysfunction have been detected by QST. These nerves are very sensible and can be irritated by inflammatory mediators such as nerve growth factor , histamine, serotonin, bradykinin, or prostaglandin .…”
Section: Scarsmentioning
confidence: 99%
“…6 Multiple mechanisms exist by which a burn scar could cause neuropathic pain. 7 Nerve entrapment within the scar tissue and neuroma formation are important in the pathogenesis of burn scar neuropathy. Studies of nerve fibers in burn patients with chronic pain revealed an increase in nociceptive nerve fibers in burn scars.…”
mentioning
confidence: 99%